Sumandar ki shehzadi - Florance iskaday (Ferozesons; Lahore, 2002)
"Sumandar Ki Shehzadi" is a mesmerizing tale of adventure and mystery, following the journey of a sea princess as she navigates the depths of the ocean and discovers the power of courage and love.